Wawasan pengembagan kebijakan pendidikan - Nur, Halimah Siti (Maliki Interdisciplinary Journal, 2026)
This research aims to analyze and develop education policy in Indonesia, particularly in addressing challenges within 3T regions (terdepan, terluar, and tertinggal – foremost, outermost, and disadvantaged areas). The primary focus of the study is on access inequality, low quality of education, infrastructure limitations, and policy formulation processes that inadequately involve local stakeholders. The research identifies opportunities and fundamental principles for creating policies that are more inclusive, adaptive, participatory, and sustainable. The findings are expected to provide concrete recommendations for improving education policies that are responsive to local needs in 3T areas, thereby enhancing overall equity and quality of education. Appropriate policies must consider internal factors such as curriculum, educator capacity, and educational infrastructure, as well as external factors such as political and economic conditions, and the influence of globalization. An ethical foundation derived from spiritual and social values, such as justice, responsibility, and respect for knowledge, needs to be an integral part of policy development.